Development of Building Energy Performance Benchmark for Hospitals - Kim, Hye Gi; Jeong, Da Woon; Kwon, Soon Jung; Kim, Sun Sook (Buildings, 2023)
The energy consumption of existing buildings depends on their physical features, climatic conditions, and business activities, such as operating hours and occupancy characteristics. It is necessary to perform a fair assessment of building energy performance considering the business activities. It has become especially necessary to collect and manage information on business activities in hospitals since hospitals operate continuously throughout the year, treating patients and using various medical equipment. This study aimed to develop a benchmark that considers business activities and to perform building energy performance assessments in hospitals using the developed benchmark. Initially, the necessary data from hospitals for assessing energy performance and developing an energy benchmark were identified. Then, survey items regarding the business activities and energy consumption of buildings were designed, and a survey was conducted at 48 general hospitals. Secondly, multiple linear regression was used to identify and normalize the major business activities affecting energy use and to develop a benchmark for energy performance assessment. Thereafter, the Energy Efficiency Ratio (EER), the result of comparing the actual energy consumption with the benchmark, was used as an index for the energy performance assessment. Thirdly, additional general hospitals were surveyed to validate the benchmark. The EER of the additional surveyed hospitals was calculated with the developed benchmark. The Energy Use Intensity (EUI) and EER of buildings were reviewed, and analysis was performed to identify why some buildings had a similar EUI but a different EER. Finally, a method to improve the benchmark is presented, and the improved benchmark model is compared with the existing model.
Keywords: building energy benchmark; building energy survey; energy efficiency ratio; hospital; operational rating; regression analysis